First record of the genus Lodosocoris Ahmad & Afzal (Hemiptera: Heteroptera: Pentatomidae: Halyini) from India with description of a new species - Salini, S.; Rabbani, M. K.; Amala, U.; Mahendiran, G. (Zootaxa, 2021)
The genus Lodosocoris Ahmad & Afzal, 1986 (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Halyini) is recorded for the first time from India. Prior to this publication, the genus was monotypic so far, containing only Lodosocoris azhari Ahmad & Afzal, 1986 from Pakistan. Herein, the genus Lodosocoris is redescribed along with the description of Lodosocoris santhae sp. nov., based on specimens from Arunachal Pradesh, a region in northeastern India. Lodosocoris santhae sp. nov is described and illustrated based on male and female genitalia. The diagnostic characters of the new species are compared with L. azhari.